2018
DOI: 10.1021/acs.est.8b02350
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation Rate Constants for Anthracene and Pyrene Are Similar in/on Ice and in Aqueous Solution

Abstract: Snowpacks contain a variety of chemicals, including organic pollutants such as toxic polycyclic aromatic hydrocarbons (PAHs). While PAHs undergo photodegradation in snow and ice, the rates of these reactions remain in debate. Some studies report that photochemical reactions in snow proceed at rates similar to those expected in a supercooled aqueous solution, but other studies report faster reaction rates, particularly at the air−ice interface (i.e., the quasi-liquid layer, or QLL). In addition, one study repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 51 publications
(127 reference statements)
2
42
0
Order By: Relevance
“…4) Vapor deposition of gas-phase guaiacol to the top surface of frozen water ice; our method here follows the same approach as previously described. 18 First, 10 ml of MQ water was placed in a beaker, covered with PE film, and frozen in a laboratory freezer at -20 °C. Once frozen, samples were removed and uncovered, and a nitrogen stream containing gas-phase guaiacol was directed at the ice surface for 15 s. Samples were then covered and placed back in a laboratory freezer.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…4) Vapor deposition of gas-phase guaiacol to the top surface of frozen water ice; our method here follows the same approach as previously described. 18 First, 10 ml of MQ water was placed in a beaker, covered with PE film, and frozen in a laboratory freezer at -20 °C. Once frozen, samples were removed and uncovered, and a nitrogen stream containing gas-phase guaiacol was directed at the ice surface for 15 s. Samples were then covered and placed back in a laboratory freezer.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Sample illumination generally followed the method described for anthracene and pyrene. 18 Sample beakers were set upright in a drilled aluminum holder to maximize heat transfer and minimize the impact of sample heating from the illumination source. Dark samples were covered with aluminum foil and placed in the illumination chamber along with illuminated samples.…”
Section: Sample Illumination Actinometry and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study of the ice spheres prepared from NaCl solution revealed that, besides the eutectic crystallization, part of the solution vitrified under the conditions of fast cooling (Imrichova et al, 2019). The differential scanning calorimetry indicated the melting of the glass at −91 • C upon progressive heating, further allowing cold crystallization of NaCl and water at −76 • C. As the ice spheres are inspected at a much higher temperature in the present study, we expect the salt to be crystalline or dissolved in liquid brine during the observations.…”
Section: Sublimationmentioning
confidence: 99%
“…The FCS can be located in the lamellae and veins between the ice crystals, (micro)pockets within the ice structure, or puddles and grain boundary grooves on the ice surface. When the mixture is cooled below the eutectic temperature (T eu ), the FCS may crystallize or vitrify (Salnikova et al, 2015;Bogdan et al, 2014;Imrichova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%